Spanning-Tree pada Graf Berarah dengan Matriks In-Degree - Tito Nurdiyanto; Ely Susanti (Department of Mathematics Education, Universitas Kuningan, 2019)
ABSTRACTGraph has a concept of tree. Tree is a connected graph which is not consist cycle. Concept of tree is an important concept because it can be used to support application of graph in any variation of science. Besides, spanning-tree is a tree in graph with every point on graph. Every graph can be formed at least there is one spanning tree. The problem of this article is how to determine the sum of spanning-tree in directed graph with matrix in-degree yang menggunakan teorema: the value of the cofactor of is equal to the number of arborescence in rooted at the vertex . Arborescence in is spanning arborescence.Keywords : spanning-tree, directed graph, matrix in-degreeABSTRAKGraf memiliki konsep tree (pohon). Tree merupakan graf terhubung yang tidak memuat siklus. Konsep tree merupakan konsep yang penting karena konsep ini dapat digunakan untuk mendukung penerapan graf dalam berbagai bidang ilmu. Sedangkan spanning-tree adalah sebuah pohon pada graf yang memuat semua titik di . Dari setiap graf dapat dibentuk paling sedikit sebuah spanning-tree. Permasalahan dalam artikel ini adalah bagaimana menentukan jumlah spanning-tree pada graf berarah dengan matriks in-degree yang menggunakan teorema: nilai kofaktor dari adalah sama dengan banyaknya arborescence pada dengan titik sebagai root. Arborescence pada juga merupakan spanning arborescence.Kata kunci: spanning-tree, graf berarah, matriks in-degree